Accuracy of probe-based confocal laser endomicroscopy (pCLE) compared to random biopsies during endoscopic surveillance of Barrett’s esophagus - Shah, Tilak; Lippman, Robert; Kohli, Divyanshoo; Mutha, Pritesh; Solomon, Sanjeev; Zfass, Alvin (Endoscopy International Open, 2018)
Background For surveillance of Barrett’s esophagus (BE), the current standard of random 4-quadrant biopsies misses 10 – 50 % of esophageal neoplasms, and does not permit real-time decision-making. Probe-based confocal laser endomicroscopy (pCLE) permits real-time in vivo histologic assessment of esophageal mucosa during upper endoscopy. Prospective studies comparing the accuracy of pCLE to 4-quadrant biopsies in routine clinical practice are lacking.Methods Consecutive patients with BE underwent high definition white light and narrow-band imaging followed by pCLE and targeted biopsy or mucosal resection. Four-quadrant biopsies were obtained during the same session. Baseline variables, real-time pCLE interpretation, and histology results were prospectively recorded. Blinded expert review of pCLE sequences and histology specimens was performed. A sample size of 64 patients was calculated a priori based on 3 % estimated prevalence of high grade dysplasia (HGD) or cancer.Results In total, 66 patients were included in the study. The prevalence of HGD or cancer was 4.55 %. Both real-time and blinded pCLE correctly identified all cases of cancer. For the primary outcome, real-time pCLE was 98 % specific but only 67 % sensitive for HGD/cancer compared to non-blinded pathologist interpretation. For HGD and cancer, inter-observer agreement was substantial between real-time and blinded endomicroscopists (kappa = 0.6). pCLE identified dysplasia in 75 % of cases where both blinded and unblinded pathology interpretation was low grade dysplasia.Conclusions pCLE demonstrates high specificity for detecting dysplasia and cancer, but lower sensitivity may limit its utility in routine BE surveillance. pCLE may have a role in confirming LGD in real-time before eradication therapy.